Advances in imaging and electron physics. the Wien filter - Tsuno, Katsushige (Advances in imaging and electron physics,, 2013)
Advances in Imaging and Electron Physics features cutting-edge articles on the physics of electron devices (especially semiconductor devices), particle optics at high and low energies, microlithography, image science and digital image processing, electromagnetic wave propagation, electron microscopy, and the computing methods used in all these domains. Key features: * Contributions from leading authorities * Informs and updates on all the latest developments in the field.